Parameters for therapeutic laparotomy in blunt trauma abdomen - Ahmad, Younis; Qadri, Arshid Iqbal; Ganie, Iqtibas Ahmad; Rashid, Muqtasid; Bhat, Gowhar Aziz (International Surgery Journal, 2018)
Background: The rapid identification of potentially life threatening intra-abdominal injury is critical for patients who sustain blunt abdominal trauma. There has been a shift from operative to non-operative management (NOM) in hemodynamically stable blunt trauma abdomen patients. The aim of present study was to determine the certain clinical and radiological parameters for therapeutic laparotomy (TL) in blunt trauma abdomen in adult patients. Methods: A prospective observational study was conducted on victims of blunt trauma who presented to our level II Emergency Department from May 2012 to June 2014. Their clinical, laboratory and radiological parameters were collected, evaluated and analyzed. A previously developed ultrasound scoring system was applied to FAST findings. Patients were followed to determine if they underwent TL or NOM. Results: A total of 7750 polytrauma patients with suspected blunt trauma abdomen underwent FAST. 338 (4.36%) patients had a positive FAST, out of which 144 were included, 93 (64.58%) patients were selected for NOM, and 51 (35.4%) patients underwent TL. NOM was successful in 76 (81.73%) patients, whereas 17 (18.27%) failed NOM and were operated. Using recursive partitioning analysis, the most important predictor for a TL, was whether the patient has an ED SBP of ≤90mmHg while other parameters include, ED pulse rate >110/min; total fast score >3; large amount of hemoperitoneum; presence of abdominal guarding, pallor and polytrauma. Conclusions: There are certain immediately available clinical, and radiological parameters, which if validated by a prospective, large sample size study could help in deriving a decision rule or even a scoring system that would determine the need for therapeutic laparotomy in blunt trauma abdomen patients.